2007
DOI: 10.1016/j.str.2007.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Rearrangements in the Carboxy-Terminal Region of SpIH Channels

Abstract: Hyperpolarization-activated cyclic nucleotide-modulated (HCN) ion channels regulate the spontaneous firing activity and electrical excitability of many cardiac and neuronal cells. The modulation of HCN channel opening by the direct binding of cAMP underlies many physiological processes such as the autonomic regulation of the heart rate. Here we use a combination of X-ray crystallography and electrophysiology to study the allosteric mechanism for cAMP modulation of HCN channels. SpIH is an invertebrate HCN chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
107
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(120 citation statements)
references
References 45 publications
11
107
2
Order By: Relevance
“…A molecular-replacement solution (log-likelihood gain = 28, Z score = 5.1) was only obtained when an ensemble of six superimposed models created by the Phyre server was provided to Phaser. The six search homology models were created from CNB-domain structures with PDB codes 1q3e, 1vp6 (21% identity; Clayton et al, 2004), 2ptm (17% identity; Flynn et al, 2007), 1cx4 (13% identity; Diller et al, 2001), 1ne6 (18% identity; Wu et al, 2004) and 2pqq (18% identity; Midwest Center for Structural Genomics, unpublished work). Electron-density maps calculated after partial refinement of the molecular-replacement solution in PHENIX (Adams et al, 2010) showed features that were not present in the search models, confirming the validity of the solution.…”
Section: Resultsmentioning
confidence: 99%
“…A molecular-replacement solution (log-likelihood gain = 28, Z score = 5.1) was only obtained when an ensemble of six superimposed models created by the Phyre server was provided to Phaser. The six search homology models were created from CNB-domain structures with PDB codes 1q3e, 1vp6 (21% identity; Clayton et al, 2004), 2ptm (17% identity; Flynn et al, 2007), 1cx4 (13% identity; Diller et al, 2001), 1ne6 (18% identity; Wu et al, 2004) and 2pqq (18% identity; Midwest Center for Structural Genomics, unpublished work). Electron-density maps calculated after partial refinement of the molecular-replacement solution in PHENIX (Adams et al, 2010) showed features that were not present in the search models, confirming the validity of the solution.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in cGMP-bound structures the cGMP molecule exists in the syn configuration, thereby facilitating a hydrogen-bond interaction of the purine ring N2 atom with residue T592 located in the β roll (Flynn et al, 2007). Several residues in helix αC (R632, R635, I636 and K638) are reported to increase selectivity of HCN2 channels for cAMP rather than for cGMP (Flynn et al, 2007;Zhou and Siegelbaum, 2007), however the reason for this selectivity is poorly understood.…”
Section: Structure Of the Hcn2 Cnbd In The Ligand-bound Statementioning
confidence: 99%
“…Several residues in helix αC (R632, R635, I636 and K638) are reported to increase selectivity of HCN2 channels for cAMP rather than for cGMP (Flynn et al, 2007;Zhou and Siegelbaum, 2007), however the reason for this selectivity is poorly understood.…”
Section: Structure Of the Hcn2 Cnbd In The Ligand-bound Statementioning
confidence: 99%
See 2 more Smart Citations